Geological framework of the pacific coast sedimentary basins, western colombia (2007)
The Pacific Coastal Province comprises the Tumaco, San Juan, Atrato and Urabá Basins. Althoughthese basins are laterally contiguous and related to an active margin (convergence of Nazcaand South America Plates) each one is characterized by a distinctive geological framework. The comparativeregional stratigraphic and structural setting of these active basins as well as their petroleumpotential is presented here using 2000 km of 2D seismic profile and information from fifteen exploratorywells. Due to the lack of biostratigraphic control within these basins, only second order sequenceswere recognized based mainly on seismic information.The Tumaco Basin is a forearc basin that comprises four second order sequences, one pre-Mioceneand three post-lower Miocene, which were deposited in deep marine environments. The base ofthe Sequence B (lower Miocene) and C (upper Miocene) were deposited in submarine fan systemsproviding turbiditic coarse clastics. The sequence A (pre-Miocene sequence) could have a thick potentialsource section of shale.The San Juan Basin represents a pull-apart basin comprising rocks from Paleocene to Quaternary,deposited mainly in deep marine environments as well as in neritic environments. The Sierra(Oligocene), Conglomerado La Mojarra (lower Miocene) and Munguidó (upper Miocene) Formations,could provide potential clastic reservoirs). In the Iró Formation also occurs competent rocks (chertsand limestones) highly fractured that represents potential fractured reservoirs. The shaly section of theIró Formation is a potential source rock in the basin.The Atrato basin is an interarc, which comprises by five second order sequences depositedmainly in deep marine environments from Late Cretaceous to Quaternary. The base of the C and Dsequences (Oligocene and middle Miocene respectively) were possibly deposited in submarine fansystems. These levels could provide sandstones and conglomerates as potential reservoirs. Sourcepotential rocks could occur in sequence A (upper Cretaceous-lower Miocene) and sequence B (lowerEocene-Oligocene).The Urabá Basin represents a backarc basin which contains five second order sequences, probablydeposited from Late Cretaceous to Quaternary, mainly in marine to transitional environments.There are three levels with coarse clastic facies. These three levels are in the upper part of theSequence B (Oligocene), in the Sequence C (Oligocene-middle Miocene) and in the Sequence D(Middle Miocene-Pliocene?), which have coarser facies toward the southwest. The Sequences A (upperCretaceous?-Eocene) and B (Eocene) contain pelitic facies in the depocenter of the basin thatcould be potential source rocks.The present study is a preliminar evaluation of the regional geology of the sedimentary basins ofthe Pacific Coast Province. This evaluation provides new ideas about the different geologic featuresof basins developed in a same tectonic setting (convergent margin) and the implications for petroleumpotential. The different characteristics of these basins could be related to differential local rate ofsubduction, different angle of the Benniof zone, transcurrent faults, etc. factors beyond the scope ofthis paper.